A Detailed Review on Quantum Computing Technologies - Saravanamoorthi, P. (Recent Research Reviews Journal, 2022)
Modern computing approaches like quantum computing are based on the remarkable occurrences of quantum mechanics. It is a combination of information theory, computer science, mathematics, and physics. The study of quantum computing includes the design and development of computer-based technologies based on quantum theory, which explains the nature and behaviour of energy and matter at atomic and sub-atomic levels. Sub-atomic particles such as electrons and photons are used in quantum computing. These particles exist in two different states (i.e., 1 and 0) based on quantum bits or qubits. Compared to conventional computers, quantum computing offers higher computing capacity, lower energy utilization, and high speed. This article reviews the state-of-the-art quantum computing technologies and different ways in which the qubits can exponentially increase the efficiency of quantum computers and sort various possibilities and identify potential solutions to different challenges.